On-board compressor water injection for civil aircraft emission reductions: range performance with fuel burn analysis - Block Novelo, David Alejandro; Igie, Uyioghosa; Nalianda, Devaiah (Elsevier, 2019)
The performance benefit of compressor water injection for a stand-alone jet engine has been investigated in previous work conducted by the authors, as well as other studies. For the same required thrust, the benefits include reduced specific fuel consumption, turbine inlet temperature and NOx emissions. The additional weight implication for aircraft (narrow and wide-body type) with their typical engine type (two and three-spool) for the varied range is investigated here. The emphasis of this study is to establish whether the performance benefit restricted to take-off and parts of the climb, offsets the additional weight penalty of the water injection system, onboard the aircraft. An in-house aircraft performance tool has been used and the changes in performance due to water injection are determined by an evaporation model previously developed. This study shows that the shortest range of 4 missions offers small overall fuel savings of 0.42% per flight cycle. The longest mission, in which the injection equipment is carried for longer (though mostly empty water tank), brings about an overall increase in fuel consumed, by about 0.05%. For the same range, the aircraft powered by a three-spool engine shows better performance. However, both aircraft equally benefit from landing and take-off NOx emission reductions of around 43%. Water Injection is shown to result in similar performance benefits as 25% take-off derate but without the penalties in fuel burn or increased take-off and climb times. Reductions in turbine inlet temperature obtained are worth considerable attention as a means of decreasing the direct operating costs of an airline.
Keywords: NOx emissions; Aircraft performance; Emissions reductions; Water injection; Derated take-off